2022
DOI: 10.1007/s12282-021-01329-7
|View full text |Cite
|
Sign up to set email alerts
|

Is adjuvant chemotherapy necessary in older patients with breast cancer?

Abstract: Background Due to the lack of clinical trials on the efficacy of chemotherapy in older patients, an optimal treatment strategy has not been developed. We investigated whether adjuvant chemotherapy could improve the survival of older patients with breast cancer in Japan. Methods We retrospectively analyzed data of patients with breast cancer aged ≥ 70 years who underwent breast cancer surgery in eight hospitals between 2008 and 2013. Clinical treatment and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The reasons for therapy decline in older patients may include duration of therapy, perceived unclear benefit of therapy, concerns regarding the potential for therapies to exacerbate preexisting medical conditions and/or cause new problems, financial concerns, and communication barriers (e.g., hearing or visual impairments that make it difficult to understand the benefits of a given cancer treatment) [12,13]. While avoidance of potentially toxic therapies is often appropriate in BC P80+ as risks may outweigh benefits, some older BC patients do benefit from adjuvant chemotherapy [14,15]. The ADVANCE (ADjuVANt Chemotherapy in the Elderly) trial assessed the feasibility of two (neo)adjuvant chemotherapy regimens in parallel-enrolling cohorts of older persons (≥ 70 years) with human epidermal growth factor receptor 2 (HER2)-negative BC [16].…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for therapy decline in older patients may include duration of therapy, perceived unclear benefit of therapy, concerns regarding the potential for therapies to exacerbate preexisting medical conditions and/or cause new problems, financial concerns, and communication barriers (e.g., hearing or visual impairments that make it difficult to understand the benefits of a given cancer treatment) [12,13]. While avoidance of potentially toxic therapies is often appropriate in BC P80+ as risks may outweigh benefits, some older BC patients do benefit from adjuvant chemotherapy [14,15]. The ADVANCE (ADjuVANt Chemotherapy in the Elderly) trial assessed the feasibility of two (neo)adjuvant chemotherapy regimens in parallel-enrolling cohorts of older persons (≥ 70 years) with human epidermal growth factor receptor 2 (HER2)-negative BC [16].…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, Morita et al. conducted a retrospective multicenter study in Japan ( 27 ). However, they did not find any significant difference in OS among older patients who received adjuvant chemotherapy or not (p = 0.333).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, its use can reportedly cause cardiac side effects, including cardiomyopathy, ischemia, arrhythmias, and myocardial necrosis, resulting in severe and irreversible left ventricular dysfunction ( 16 , 17 ). Two main mechanisms can explain this cardiotoxicity: (i) anthracyclines cause myocyte DNA damage, bind to topoisomerase IIβ and disrupt replication ( 18 , 19 ); (ii) anthracyclines form complexes with intracellular iron, which in turn generate reactive oxygen species that damage DNA, proteins, and lipids, including mitochondrial membranes, and accelerate myocyte death ( 20 , 21 ). In this regard, Howard et al showed that doxorubicin-based adjuvant chemotherapy for breast cancer could cause arrhythmias and conduction abnormalities in 2.6% of patients compared to 1% of patients who did not receive doxorubicin ( 4 ).…”
Section: Discussionmentioning
confidence: 99%